2016
DOI: 10.1093/protein/gzw030
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofN-linked glycosylation on the activity and other properties of recombinant endoglucanase IIa (Cel5A) fromPenicillium verruculosum

Abstract: Endoglucanase IIa from Penicillium verruculosum (PvCel5A) has three potential N-glycosylation sites: Asn19, Asn42 and Asn194. In order to study the role of N-glycosylation, the wild type (wt) PvCel5A and its mutant forms, carrying Asn to Ala substitutions, were cloned into Penicillium canescens All forms of the rPvCel5A were successfully expressed and purified for characterization. The MALDI-TOF mass spectrometry peptide fingerprinting showed that N-glycans linked to Asn42 and Asn194 represent variable oligosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In particular, these properties were demonstrated for CBHs from P. funiculosum, P. pulvirrolum, P. verruculosum, and P. canescens [23,24]. It should be noted that one of the reasons for such a high specific activity in the case of CBH I and CBH II from P. verruculosum is the optimal distribution of N-linked glycans on the surface of the catalytic domain of these enzymes [25,26].…”
Section: Advantages Of the Enzymatic Complex Of Filamentous Fungi Penmentioning
confidence: 89%
See 1 more Smart Citation
“…In particular, these properties were demonstrated for CBHs from P. funiculosum, P. pulvirrolum, P. verruculosum, and P. canescens [23,24]. It should be noted that one of the reasons for such a high specific activity in the case of CBH I and CBH II from P. verruculosum is the optimal distribution of N-linked glycans on the surface of the catalytic domain of these enzymes [25,26].…”
Section: Advantages Of the Enzymatic Complex Of Filamentous Fungi Penmentioning
confidence: 89%
“…Although it has been shown that when the substrate is more recalcitrant, the synergism in reducing sugar production decreases [32], as the interaction between cellulase and cellulose is a complex process, the understanding of the molecular mechanisms of cellulose hydrolysis by cellulase mixtures is highly essential and remains to be elucidated. specific activity in the case of CBH I and CBH II from P. verruculosum is the optimal distribution of N-linked glycans on the surface of the catalytic domain of these enzymes [25,26].…”
Section: Cellulases Synergismmentioning
confidence: 99%
“…244 Similarly, glycosylation was correlated with improved activity of the cellobiohydrolases of GH families 5, 6, and 7. 245248 …”
Section: Tertiary Protein Structuresmentioning
confidence: 99%
“…Frequently, more complex eukaryotic expression systems, like Komagataella phaffii (formerly known as Pichia pastoris) or Yarrowia lipolytica, have to be used to express eukaryotic xylanases from A. niger, Trichioderma harzianum, Hypocrea orientalis, or Trichioderma reesei (He et al, 2009;Wang et al, 2014;Li et al, 2018) as they have the advantage of correct N-and O-glycosylation. The glycosylation can have different effects like enhancement of solubility (Solá and Griebenow, 2009), increased activity, as shown for the endo-cellulase IIa from Penicillium verrucosum (Dotsenko et al, 2016), or enhanced stability (Sarkar and Wintrode, 2011). On the other hand, there are a number of reports showing the expression of xylanases in E. coli (Basaran et al, 2001;Le et al, 2011) but having the disadvantage of either being periplasm bound to the E. coli or having low activity (about 30 U/mg).…”
Section: Discussionmentioning
confidence: 99%